FUNDAMENTALS OF INTERACTION WITH LAW ENFORCEMENT AGENCIES IN TEACHING CRIMINAL LAW (Scientific journal of the Fergana State University, 2023)
Each country in the world has its own national legal system, and their systems of national-state, administrative-territorial and political administrations differ to a certain extent from others. These differences also apply to law enforcement agencies. The diversity of legal consciousness and legal culture of citizens also affects the powers, rights and obligations of law enforcement agencies. In the Republic of Uzbekistan, law enforcement agencies have their place in the system of public administration, and each body operates within the powers established by law. Employees serving in the field are not limited to law enforcement activities, but also contribute to raising the legal awareness and legal culture of the population. They can also help in education. Therefore, a scientifically based qualitative methodology is of great importance in the teaching of legal subjects in modern education. It should serve to improve the level of professional training of students, the quality of educational activities and their interest in their profession. In particular, it will be effective to establish relations with law enforcement agencies when organizing classes on the subject of criminal law. Its necessity is disclosed in this article. There are also recommended topics for organizing meetings with law enforcement.